The maritime landscape of the Isthmus of Panamá - Delgado, James P.; Hernández Mendizabal, Tomás, 1940-; Hanselmann, Frederick H.; Rissolo, Dominique (Gainesville : University Press of Florida, 2016)
Este trabajo explora la historia marítima del istmo de Panamá, a través del uso prehistórico colonial española a la construcción del canal y el tráfico marítimo de hoy en día.
Introduction: Setting and context -- The isthmus in the Pre-European world -- The isthmus encountered and conquered, 1501-1540 -- The isthmus challenged and fortified, 1540-1738 -- Buccaneers, pirates, the Morgan attack, and the Scottish at Darién -- The isthmus in "decline," 1739-1848 -- The isthmus during and after the "Fiebre del Oro," 1849-1861 -- Canal dreams and realities, 1861-1902 -- Fortification and control, 1903-2015 -- Conclusion. - Notes. - References. - Index.
Incluye referencias bibliográficas (páginas [243]-272) e índice.
Keywords: EXCAVACIONES ARQUEOLOGICAS -- PANAMA; ARQUEOLOGIA SUBMARINA -- PANAMA; ISTMOS -- PANAMA -- ANTIGUEDADES; PANAMA -- HISTORIA; PANAMA -- ANTIGUEDADES